2010
DOI: 10.2139/ssrn.2104411
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic Optimization Methods for Dynamic Panel Data Model Selection: Application on the Russian Innovative Performance

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 44 publications
0
21
0
2
Order By: Relevance
“…In particular, we apply heuristic optimization techniques as advocated by e.g. Savin and Winker (2012), Acosta-González and Fernández-Rodríguez (2007) and Kapetanios (2007). These are able to deal with non-smooth, discrete optimization problems.…”
Section: Selecting Interactions Using Heuristic Optimization Techniqumentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, we apply heuristic optimization techniques as advocated by e.g. Savin and Winker (2012), Acosta-González and Fernández-Rodríguez (2007) and Kapetanios (2007). These are able to deal with non-smooth, discrete optimization problems.…”
Section: Selecting Interactions Using Heuristic Optimization Techniqumentioning
confidence: 99%
“…Recently, Acosta-González and Fernández-Rodríguez (2007), Kapetanios (2007) and Savin and Winker (2012) have shown that heuristic optimization techniques based on information criteria as objective function deliver promising results in selecting regressors in different model selection set-ups of multiple regression models. 7 Kapetanios (2007) documents an outperformance of Simulated Annealing (SA) and Genetic Algorithms (GA) as two classical heuristic methods over PcGets.…”
Section: Selecting Interactions Using Heuristic Optimization Techniqumentioning
confidence: 99%
See 3 more Smart Citations